2017
DOI: 10.1016/j.celrep.2017.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Uroplakin 3a+ Cells Are a Distinctive Population of Epithelial Progenitors that Contribute to Airway Maintenance and Post-injury Repair

Abstract: There is evidence that certain club cells (CCs) in the murine airways associated with neuroepithelial bodies (NEBs) and terminal bronchioles are resistant to the xenobiotic naphthalene (Nap) and repopulate the airways after Nap injury. The identity and significance of these progenitors (variant CCs, v-CCs) have remained elusive. A recent screen for CC markers identified rare Uroplakin3a (Upk3a)-expressing cells (U-CCs) with a v-CC-like distribution. Here, we employ lineage analysis in the uninjured and chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 26 publications
2
77
0
Order By: Relevance
“…Basal cells are present throughout human conducting airways, but are confined to the trachea and primary bronchi of mice (Boers et al, 1998; Nakajima et al, 1998). In mice, it is clear that the dome-shaped club cells in the bronchioles act as stem cells for day-to-day airway epithelial maintenance and repair (Giangreco et al, 2009, 2002; Hong et al, 2001; Rawlins et al, 2009b) and can even contribute to the alveolar epithelium following injury (Guha et al, 2017). In contrast, club cells within the pseudostratified mouse trachea are progenitors that do not exhibit long-term self-renewal, but do divide for a limited time and can produce new ciliated cells (Rawlins et al, 2009b; Watson et al, 2015).…”
Section: An Introduction To Human Lung Developmentmentioning
confidence: 99%
“…Basal cells are present throughout human conducting airways, but are confined to the trachea and primary bronchi of mice (Boers et al, 1998; Nakajima et al, 1998). In mice, it is clear that the dome-shaped club cells in the bronchioles act as stem cells for day-to-day airway epithelial maintenance and repair (Giangreco et al, 2009, 2002; Hong et al, 2001; Rawlins et al, 2009b) and can even contribute to the alveolar epithelium following injury (Guha et al, 2017). In contrast, club cells within the pseudostratified mouse trachea are progenitors that do not exhibit long-term self-renewal, but do divide for a limited time and can produce new ciliated cells (Rawlins et al, 2009b; Watson et al, 2015).…”
Section: An Introduction To Human Lung Developmentmentioning
confidence: 99%
“…During embryonic development, cells surrounding PNECs, i.e., presumptive CLCs, remain undifferentiated [ 30 ]. CLCs/vCE cells appear to be resistant to naphthalene ablation because, unlike CCs, they do not express the cytochrome P450 2F2 isozyme [ 12 , 43 , 44 ]. It has been reported that CLCs in postnatal lungs show the capacity to regenerate both CCs and ciliated cells [ 45 , 46 ], but that severe epithelial injury is required to activate the stem cell niche for repair [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,10,11 Most recently, Upk3a has also been proposed to identify a rare subset of club cells with differentiation potentials. 12 In alveoli, type II cells (AEC2) act as stem cells to produce both type I and II alveolar cells. 13,14 The BMP family members play key roles in lung development and homeostasis.…”
mentioning
confidence: 99%